Plan estratégico para la creación de una oficina consultora de comercio exterior en la ciudad de Otavalo - Mueces, Doris A. (2017)
The present project consists of a proposal for the creation of a consulting office to provide advisory services and training on foreign trade issues to small and medium-sized enterprises in the city of Otavalo, with the aim of helping SMEs to Activities and can solve the problems that arise in the processes of export and import.